Associations between burnout and career disengagement factors among general practitioners: a path analysis - Christos Grigoroglou; Christos Grigoroglou; Mark Hann; Mark Hann; Alexander Hodkinson; Alexander Hodkinson; Salwa S. Zghebi; Evangelos Kontopantelis; Evangelos Kontopantelis; Darren M. Ashcroft; Darren M. Ashcroft; Darren M. Ashcroft; et al. (Frontiers in Public Health)
BackgroundBurnout is associated with career disengagement among general practitioners (GPs), but the underlying mechanisms of this association remain poorly understood.ObjectiveThis study examined the pathways linking burnout to career disengagement factors among GPs.MethodsAn 11-item online questionnaire, including validated abbreviated measures of burnout outcomes (single items on emotional exhaustion (EE) and depersonalisation), career disengagement factors (intention to quit patient care, work–life balance, presenteeism and job satisfaction), and demographic information, was distributed to a random sample of GPs in England between December 2019 and April 2020. Correlations between burnout outcomes and disengagement factors were assessed, followed by a path analysis using a generalized structural equation model, to examine directional relationships between burnout outcomes and survey variables.ResultsA total of 351 GPs from 57 different medical practices completed the questionnaire. Up to one in four GPs (22.5%) experienced emotional exhaustion, while up to one in three (27.4%) experienced depersonalisation on a weekly basis. In addition, one in three GPs (33.3%) expressed a moderate-to-high intention to quit patient care within the next 5 years. Moreover, one in five GPs (18.8%) reported job dissatisfaction, two in five GPs (40.7%) indicated poor work–life balance, and up to one in two GPs (27.4%) reported presenteeism in the past year. In the path analysis, intention to quit patient care had significant direct associations with both job satisfaction and burnout and significant indirect associations (via burnout) with work–life balance and presenteeism. GP demographics were excluded from the path analysis because they exhibited very weak correlations with dimensions of burnout and work engagement factors.ConclusionThese findings highlight the urgent need for interventions and policies aimed at addressing burnout and improving job satisfaction to retain GPs. In addition, improving work–life balance and reducing presenteeism could serve as effective early preventative measures to reduce burnout and job dissatisfaction and, in turn, retain GPs.